Effects of Background Context for Objects in Photographic Targets on Remote Viewing Performance - Katz, Debra Lynne; Lane, James D.; Bulgatz, Michelle (Journal of Scientific Exploration, 2022)
Photographic images of physical objects are common targets in remote viewing projects today. This exploratory experiment investigated whether the background within which the object is positioned may impact the accuracy of remote viewing. Twelve experienced remote viewers each completed 30 open-response, triple-blind remote viewing trials, requiring them to utilize extrasensory perception to describe the photographic image they would receive via email a few days later. Investigators created a photographic target pool of complex objects set within one of three background conditions: 1) White: devoid of information 2) Normal: a setting in which the object would typically be found. 3) Unusual: a setting which the object would typically not be found. Participants completed a total of 360 in-depth transcripts consisting of 8460 written descriptors and 1472 sketches. Two methods were used to analyze the transcripts for accuracy, the traditional sum of ranks matching procedure and an exploratory method involving the scoring of each item and sketch by both the participant and an independent judge. These two methods revealed significant but opposite differences for photographic targets of objects set within white backgrounds compared to the other two backgrounds. Better scores for targets with a white background were found for the traditional matching procedure, but worse scores were found for this background when each item and sketch were rated individually. In addition, the individual items and sketches were found to describe the target object more frequently than the background when normal or unusual backgrounds were present. Results suggest that object background can affect the outcome of remote viewing sessions, although the effect may depend on the scoring method applied. Keywords: Remote viewing, target material, extrasensory perception, anomalous cognition, photographic target material.